Tumor suppressor P73-loaded PLGA/chitosan nanoparticles: a novel non-viral gene delivery system for oral squamous cell carcinoma therapy - Ichwan, Solachuddin J. A.; Taher, Muhammad; Doolaanea, Abd Almonem; Mohamed, Farahidah (2019)
Oral squamous cell carcinoma (OSCC) is the sixth most common malignancy worldwide. Cancer gene therapy is a treatment method that has been developed to selectively destroy cancer cells by using genetic material injected into tumor tissue. p73β tumor suppressor gene, has been considered as a potential gene therapy agent as it has been found to be an important determinant of chemosensitivity in oral squamous cell carcinoma (OSCC). This current study was aimed to fabricate PLGA-Chitosan nanoencapsulated plasmid DNA p73β and analyze its anticancer potential in OSCC cell lines. Herein, we demonstrate that the size of PLGA/Chitosan nanoparticles (NPs) is an important determinant for the optimal uptake by the KON and HSC-3 cells. Nanoparticles size less than 800 nm were found to have the optimal uptake rate by HSC-3, whereas KON only up-took NPs smaller than 600 nm. We assessed the gene/protein expressions and apoptotic potential of p73-NPs in comparison to plasmid p73 lipofectamine-transfection method on KON and HSC-3 cells. The real time PCR and Western Blotting revealed that nanoparticles transfection exhibited more sustained level of p73 overexpression than those shown by lipofectamine method. Whilst the p73 expression began to fade away by 4th days and 5th days post transfection (KON and HSC-3 cells, respectively), the p73 protein expression retained up to 12 and 10 days of post-exposure to nanoparticles in KON and HSC-3 cells, respectively. On the other hand, flow cytometry and Caspase 3/7 activity analyses demonstrated that the p73 nanoparticles induced apoptosis on both cell lines with comparable level to those induced by lipofectamine-transfection method. Co-incidentally, we also observed that lipofectamine-mediated p73 treated cells showed slight reduction of Survivin (a member of the inhibitor of apoptosis) protein expression. In contrast, the p73-nanoparticles treated cells markedly decreased the level of Survivin expression in both cells. This finding suggest that p73-nanoparticles was more potent in lowering the cancer cells survival. Furthermore, quantitative analysis of mRNA expressions of p73 target genes namely p21, Bax, PUMA, and Apaf1 revelaed that the expression levels of these genes corresponded to the p73 expression induced by the nanoparticles. Taken together, we concluded that p73β-loaded PLGA/chitosan nanoparticles are capable to release of p73β gene expression at sustained level while inducing apoptosis on OSCC cells. This finding will give insight into the promising use of a novel non-viral, cheap, and eco-friendly p73β-based gene therapy in OSCC management.